New approaches for understanding the potential role of microbes in Alzheimer's disease - Heather E. Whitson; William A. Banks; Monica M. Diaz; Bess Frost; Manolis Kellis; Richard Lathe; Kenneth E. Schmader; Serena S. Spudich; Rudolph Tanzi; Gwenn Garden (Brain, Behavior, & Immunity - Health, 2024)
Alzheimer's disease (AD) involves a complex pathological process that evolves over years, and its etiology is understood as a classic example of gene-environment interaction. The notion that exposure to microbial organisms may play some role in AD pathology has been proposed and debated for decades. New evidence from model organisms and -omic studies, as well as epidemiological data from the recent COVID-19 pandemic and widespread use of vaccines, offers new insights into the “germ hypothesis” of AD. To review new evidence and identify key research questions, the Duke/University of North Carolina (Duke/UNC) Alzheimer's Disease Research Center hosted a virtual symposium and workshop: “New Approaches for Understanding the Potential Role of Microbes in Alzheimer's disease.” Discussion centered around the antimicrobial protection hypothesis of amyloid accumulation, and other mechanisms by which microbes could influence AD pathology including immune cell activation, changes in blood-brain barrier, or direct neurotoxicity. This summary of proceedings reviews the content presented in the symposium and provides a summary of major topics and key questions discussed in the workshop.